2020
DOI: 10.20944/preprints202009.0730.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using PCM in two proposed residential buildings in Christchurch, New Zealand

Abstract: A characteristic feature of lightweight constructions is their low thermal mass which causes high internal temperature fluctuations that require high heating and cooling demand throughout the year. Phase Change Materials (PCMs) is effective in providing thermal inertia to low thermal mass buildings. The aim of this paper is to analyse the thermal behaviour of two proposed lightweight buildings designed for homeless people and to investigate the potential benefit achievable through the use of different types of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…-Reduction in indoor temperature fluctuations and maintaining thermal comfort [5,7,9]; -Reduction in energy consumption for heating/cooling and efficient use of HVAC units [2,17]; -Enabling peak-load shifting of electricity and producing significant energy savings [19,20]. Combined with lower prices being available during off-peak periods, the associated cost savings could provide the public with an incentive to use PCM and improve the thermal performance of their buildings [19,20]; -Improve the feasibility and distribution of both passive and active solar heating.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 3 more Smart Citations
“…-Reduction in indoor temperature fluctuations and maintaining thermal comfort [5,7,9]; -Reduction in energy consumption for heating/cooling and efficient use of HVAC units [2,17]; -Enabling peak-load shifting of electricity and producing significant energy savings [19,20]. Combined with lower prices being available during off-peak periods, the associated cost savings could provide the public with an incentive to use PCM and improve the thermal performance of their buildings [19,20]; -Improve the feasibility and distribution of both passive and active solar heating.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Technical analysis of the global energy consumption highlighted the excessive consumption of energy in the building sector [ 3 ], of which significant improvements could be made to the HVAC operations [ 4 ]. Through the process of conducting many research projects, as published in “ Thermal Energy Storage with Phase Change Materials ” [ 5 ], the authors examined the factors affecting the buildings of lightweight materials and diagnosed the important role played by the thermal mass of the building [ 6 , 7 ] and the lack of thermal mass present in lightweight building materials [ 8 ]. The authors of the same book [ 5 ] also answered the core question of how the thermal mass of new and existing buildings, particularly those made from lightweight materials, can be increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have shown that the use of phase change materials (PCMs) 10,11 could help improve the thermal comfort in different buildings. 12,13 PCMs were incorporated in both residential 14 and public buildings. 15 Sage-Lauck and Sailor 16 evaluated the impacts of using PCMs on indoor thermal comfort in an insulated residential building using experimental and numerical methods.…”
Section: Introductionmentioning
confidence: 99%